'A Place full of Trade': Placing an Early Modern Chinese Town in Global Cultural History. Issue 2 (October 2020) - Gerritsen, Anne
Abstract : This article focuses on the history of Wuchengzhen 吳 城 鎮, a small town in the inland province of Jiangxi. It explores the history of the town between 1500 and 1850 in terms of both its local significance as an entrepot for trade in grain and tea and its global connections to early modern Europe, by way of the trade in porcelain. The question this paper explores concerns the juxtaposition between, on the one hand, the idea gained from global historians, that during the early modern period, globally traded commodities like tea and porcelain situate a small town like this in a globalized, perhaps even unified or homogenous, world, and on the other hand, the insight gained from cultural historians, that no two people would ever see, or assign meaning to, this small town in the same way. Drawing on this insight, the history of Wuchengzhen is explored on the basis of different textual (administrative records, local gazetteers, merchant manuals) and visual sources (maps and visual depictions of the town), exploring the ways in which the different meanings of the town are constructed in each. The combination of global and cultural history places Wuchengzhen on our map of the early modern world.